Evidence for a hypothalamic disturbance in cyclical oedema. Issue 6379 (28th May 1983) - Young, J B; Brownjohn, A M; Chapman, C; Lee, M R
Abstract : Fourteen women with cyclical oedema and six healthy female controls were investigated by use of a test in which thyrotrophin releasing hormone and luteinising hormone releasing hormone were given. Significant differences in the responses of prolactin, luteinising hormone, and follicle stimulating hormone were observed in the patients. These findings suggest that there may be a hitherto unrecognised hypothalamic defect in cyclical oedema that may account for some of the previously unexplained clinical features and lead to a more rational therapeutic approach in the management of the disorder.